1954
DOI: 10.1021/ac60087a066
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Micro Quantities of Pyrethroids

Abstract: Ix recent attempts to estimate small quantities of pyrethrins in flour which had been stored in pyrethrum-treated cotton bags ( 14), the extraction from cotton, paper, and other media was found to be difficult and there were apparent limitations in the accuracy of the analysis of pyrethroids-i.e., chrysanthemum esters of alkyl cyclopentenolones by the Association of Official Agricultural Chemists (AOAC) 1950 Method (1). Since then, these problems have been given further consideration in this

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1955
1955
1976
1976

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…A short while later (10) Harper and Sleep observed that chrysanthemumonitrile contains 73 % of this isomer. By means of a modified AOAC method (1), the quantity of ¿'/•cms-chrysanthemummonocarboxylic acid present in the racemic acid was found to be nearly identical with that reported in this paper (19).…”
supporting
confidence: 71%
“…A short while later (10) Harper and Sleep observed that chrysanthemumonitrile contains 73 % of this isomer. By means of a modified AOAC method (1), the quantity of ¿'/•cms-chrysanthemummonocarboxylic acid present in the racemic acid was found to be nearly identical with that reported in this paper (19).…”
supporting
confidence: 71%
“…In the colorimetric procedure of Schreiber and McClellan (7) suitable for pyrethroid compounds such as allethrin, dimethrin, and pyrethrins, the Denigés reagent is reduced by chrysanthemumic acid, yielding various shades of color such as the salmon red, turning to a raspberry red, in contrast to the pink to stable purple obtained for allethrin and chrysanthemumic acid (racemic mixture of the dl-cis and dltrans acids), respectively.…”
Section: Chromatographic and Dimethrin Isomersmentioning
confidence: 99%